2023
DOI: 10.3390/biomedicines11061679
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155-5p Attenuates Vascular Smooth Muscle Cell Oxidative Stress and Migration via Inhibiting BACH1 Expression

Abstract: The malfunction of vascular smooth muscle cells (VSMCs) is an initiating factor in the pathogenesis of pathological vascular remodeling, including hypertension-related vascular lesions. MicroRNAs (miRNAs) have been implicated in the pathogenesis of VSMC proliferation and migration in numerous cases of cardiovascular remodeling. The evidence for the regulatory role of miR-155-5p in the development of the cardiovascular system has been emerging. However, it was previously unclear whether miR-155-5p participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our previous research has been shown that BACH1 facilitates VSMC migration [21]. In the present study, we found that the content and level of BACH1 in EVs of SHRs were much higher than that of WKYs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our previous research has been shown that BACH1 facilitates VSMC migration [21]. In the present study, we found that the content and level of BACH1 in EVs of SHRs were much higher than that of WKYs.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, we have found that miR-155-5p attenuates VSMC oxidative stress and migration via inhibiting BTB and CNC homology1 (BACH1) expression [21], which increases in the EVs from macrophages of spontaneously hypertensive rats (SHRs), compared with that of Wistar-Kyoto rat (WKYs). BACH1, as a stress-reactive transcription factor, can enhance oxidative stress, regulate cell cycle and immune function [22].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in non-small cell lung cancer (NSCLC) tissues, miR-196a was significantly upregulated, which in turn resulted in NSCLC cell migration and invasion, partially via downregulation of HOXA5 (Liu et al, 2012), and miR-155 has been implicated in with inflammation and cardiovascular diseases (Schroen and Heymans, 2012). In addition, previous reports characterized miR-155 and miR-122 as suppressors of cell migration and oxidative stress, including vascular SMC (Tong et al, 2023), whereas knockdown of miR-155-5p results in increased proliferation and migration of human brain micro-vessel ECs (Liu et al, 2015). Another significantly Schematic showing regulatory mechanisms obtained from the integrative analysis of the lncRNA-miRNA-mRNA interactions in OCT4 deficient SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overexpression of miR-155-5p and downregulation of BACH1 repressed the migration of VSMCs. The suppression of BACH1 by miR-155-5p was sufficient to decrease the migration and oxidative stress in VSMCs [ 37 ]. A recent study published by Li et al using a knock-out model of miR-214 in VSMCs investigated the role of miR-214 in vascular smooth muscle cells by quantification of the expression of contractile markers including smooth muscle actin, smooth muscle myosin heavy chain, and calponin.…”
Section: Discussionmentioning
confidence: 99%